Desarrollo de un sistema Web Server para el monitoreo de una estación de nivel. - Basantes Osorio, Edison Paul (2021)
The present degree work had as objective the design of a web page and an executable that allows a better interaction, for the control and monitoring of a level station, which can be visualized in any electronic device that establishes a connection to internet, this allows to obtain the data that sends the station in real times, the programming was carried out by means of the language of JavaScript which is used by the software Node-Red, allowing the interface with the PLC S7-1200 and the mini Pc I5 of mark Lenovo of fourth generation, meanwhile for the executable that was realized in the program Unity with the language of programming of C#, in this execution the user will be able to be the administrator or the operator with his respective key, the program allows the interaction of our users observing the data in the page and in the executable in real time without the need to be in the place of work, this means that the operator will be able to receive the data in any part of the world. Nowadays these modern tools in the industrial area, are more accepted because they prefer the control of a station through the WEB, also when presenting these options of control and monitoring they minimize the costs in their elaboration by the implementation of tools with free softwares, allowing the acquisition of data in real time, for management.